PENERAPAN STRATEGI PREDICT, ORGANIZE, REHEARSE, PRACTICE AND EVALUATE (PORPE) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Mhd Iqbal Maulana; Nurhaswinda Nurhaswinda; Rizki Amalia; Putri Hana Pebriana; Fadhilaturrahmi Fadhilaturrahmi (Jurnal Dedikasi Pendidikan, 2023)
This research was motivated by the low results of students' comprehension skills on my diversity material in class IV SDN 019 Lubuk Agung. This research method was classroom action research (PTK) which was carried out in two cycles.The subject of this research was class IV students, totaling 20 students. Data collection techniques were in the form of documentation, observation and tests. While technical data analysis uses quantitative and qualitative data analysis. Based on the results of data analysis, it can be seen that the results of students' reading comprehension skills increased after the action, the average completeness of the collaboration results In the pre-action activities, the class average value was 74.75 with classical completeness of 45%, increased in cycle 1 meeting 1 to 75.5 with classical completeness  of  50%,  increased in  cycle 1  meeting  2  to  78  with  a classical mastery of 5 5%. The class average score in cycle 2 meeting 1 was 82.25 with classical completeness of 70% and increased in cycle 2 meeting 2 which was 88.5 with classical completeness of 85%. So it can be concluded that the application of the Predict, Organize, Rehearse, Practice And Evaluate (PORPE) strategy can improve the reading comprehension skills of grade IV students at SDN 019 Lubuk Agung.